A Characterization of Brain Area Activation in Orienteers with Different Map-Recognition Memory Ability Task Levels—Based on fNIRS Evidence - Yang Liu; Su Lu; Jingru Liu; Mingsheng Zhao; Yue Chao; Pengyang Kang (Brain Sciences, 2022)
Background: Mapping memory ability is highly correlated with an orienteer’s level, and spatial memory tasks of different difficulties can reveal the spatial cognitive characteristics of high-level athletes. Methods: An “expert–novice” experimental paradigm was used to monitor behavioral performance and changes in cerebral blood oxygen concentration in orienteering athletes with tasks of different difficulty and cognitive load using functional near-infrared spectroscopic imaging (fNIRS). Results: (1) there was no difference between high-/low-level athletes’ map recognition and memory abilities in the non-orienteering scenario; (2) with increasing task difficulty, both high-/low-level athletes showed significantly decreasing behavioral performance, reduced correctness, longer reaction time, and strengthened cerebral blood oxygen activation concentration. There was no significant difference in L-DLPFC cerebral oxygen concentration between high-/low-level athletes in the simple map task, and the cerebral oxygen concentration in all brain regions was lower in the expert group than in the novice group in the rest of the task difficulty levels; (3) the correctness rate in the expert group in the complex task was closely related to the activation of the right hemisphere (R-DLPFC, R-VLPFC). Conclusions: Experts have a specific cognitive advantage in map-recognition memory, showing higher task performance and lower cerebral blood oxygen activation; cognitive load constrains map-recognition memory-specific ability and produces different performance effects and brain activation changes on spatial memory processing.